IMPLEMENTASI SERVICE ORIENTED ARCHITECTURE (SOA)MENGGUNAKAN TEKNOLOGI WEB SERVICE - Prasetyo, Hendro Joko (Jurnal Informatika, 2012)
In Service Oriented Architecture (SOA), an application is modeld as composition of a set of service that is served by a component. Location of the component can be found by client dynamically, using discovery mechanism to search location of the component. Thus, client can invoke the service dynamically too. There are some technologies used to apply SOA, including CORBA, DCOM, RMI, Web Service. Those technologies have advantages and disadvantages. CORBA, DCOM, and RMI are closed system. Whereas Web Service are web based non-proprietary system. So that, in further trend web service technology will be widely used. This paper will describe how SOA is and how to apply that architecture in web service technology. Â  Keywords : SOA, Web Service, Proprietary.